Is formal physical therapy necessary after reverse total shoulder arthroplasty? A single-blinded, randomized controlled trial - Andrew B. Rees, MD; G. Dillon Graham, MD; Joseph M. Burger, MD; Bryan M. Saltzman, MD; Shadley Schiffern, MD; Patrick Connor, MD; Nady Hamid, MD (JSES International)
Background: Formal, supervised physical therapy (SPT) is a mainstay in the postoperative rehabilitation protocol after reverse shoulder arthroplasty. However, recent studies have called into question its superiority over alternative approaches. The purpose of this study was to compare, in a randomized controlled trial, the effectiveness of an unsupervised home therapy (UHT) program to SPT on patient-reported outcomes for patients undergoing reverse shoulder arthroplasty. Methods: In this prospective, single-center study, 59 patients aged 60-85 undergoing primary reverse shoulder arthroplasty were randomly assigned to either SPT (n = 30) or UHT (n = 29) groups. The UHT group followed a detailed physical therapy manual provided before discharge. Exclusion criteria included a history of ipsilateral shoulder infection, autoimmune or neuromuscular disease, and a need for postdischarge rehabilitation facility care. The primary outcome measure was the American Shoulder and Elbow Surgeons score at 1 year postoperatively. Secondary outcomes included Simple Shoulder Test, Constant score, visual analog scale, patient satisfaction, and range of motion at 3 months and 1 year postoperatively. An independent examiner blinded to group assignment evaluated these outcomes. Results: Results showed no significant difference in American Shoulder and Elbow Surgeons scores between the SPT group (mean 77.6) and UHT group (mean 81.1) at 1 year postoperatively (P = .501). Despite limited in-person follow-up rates, range of motion measurements showed no significant differences between groups at either 3 months (41 patients) or 1 year (25 patients) postoperatively. Both groups demonstrated comparable results in Constant scores, visual analog scores, and patient satisfaction measures. Neither group required any reoperations during the study period. Conclusion: This study suggests that self-directed home therapy following reverse shoulder arthroplasty may be a viable alternative to formal SPT. Although the findings were limited by reduced in-person follow-up rates, which may have underpowered certain comparisons, the results consistently showed no significant differences between the two approaches across multiple outcome measures. These findings have important implications for patients who face barriers to accessing formal physical therapy due to circumstances, cost, or comorbidities, suggesting that a well-structured home exercise program may provide comparable outcomes. Future research with larger sample sizes and higher follow-up rates would be valuable to confirm these findings.